(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1865)
This article is an account of the excavation of three sites in Shetland, at which he found a stone cist, a wooden drinking cup, and the remains of a dry stone dyke. Dimensions are provided for each of these finds and the circumstances of their discovery is noted.